FACTORS INFLUENCING ONLINE PURCHASE DECISION OF TIKTOKSHOP CUSTOMERS IN MANADO - Dewa Ayu Putri; David P. E. Saerang; Shinta J. C. Wangke (Universitas Sam Ratulangi, 2022)
In the world of marketing, buying decisions that will be made by someone is one of the important things to do analysis. This is important because it can help marketers to understand what the target market needs and also what the target market wants so that marketers can make a profit. This research was conducted with the aim of analyzing what factors influencing online purchase decision of tiktokshop customers in manado by using the factor analysis method for data reduction with the aim of summarizing the observed factors. The results of the validity test and reliability test show that the instrument in this study can be used because it meets the requirements. The results of the study showed that all the 20 variable factors met the requirements based on the KMO table and Bartlett's test. The results of the factor analysis test show that all factor items have the same criteria so that they can be used as a single factor. Among 20 factors tested, there are 4 factors that give the most dominant influence which are convenience (0.783), Perceived ease of used (0.777), perceived benefit (0.770), and quality of information (0.763).